2023
DOI: 10.1007/s00167-023-07554-1
|View full text |Cite
|
Sign up to set email alerts
|

The Matsudai Knee Osteoarthritis Survey showed the longitudinal changes of knee phenotypes in alignment and structure during 23–28 years

Yasuyuki Tomiyama,
Tomoharu Mochizuki,
Hiroshi Koga
et al.

Abstract: Purpose The longitudinal changes in alignment and structure, including the joint line and cortical bone thickness (CBT) of the femur and tibia, and knee phenotype in patients with knee osteoarthritis (OA) remain unknown. The aim of this retrospective study was to clarify the longitudinal changes in matched healthy subjects. Methods The follow-up Matsudai Knee Osteoarthritis Survey was administered between 23 and 28 years. This study included 285 healthy knees from 235 females with an average age of 53 ± 6 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The reason for the low involvement of the femoral joint‐line inclination in the present study is that the femoral joint‐line inclination did not significantly differ according to the KL grade. However, a previous longitudinal study showed that the average change in the femoral joint‐line inclination was 1–2° in the same participants over 20–30 years [ 20 ]. In a cross‐sectional study such as the present study, it is assumed that the difference is only to the extent that it is absorbed by measurement error, which is why no difference was observed in the KL grade, as in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for the low involvement of the femoral joint‐line inclination in the present study is that the femoral joint‐line inclination did not significantly differ according to the KL grade. However, a previous longitudinal study showed that the average change in the femoral joint‐line inclination was 1–2° in the same participants over 20–30 years [ 20 ]. In a cross‐sectional study such as the present study, it is assumed that the difference is only to the extent that it is absorbed by measurement error, which is why no difference was observed in the KL grade, as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An epidemiological study on knee OA was conducted between 1979 and 2022 using the Matsudai Knee Osteoarthritis Survey [ 4 , 20 ]. The study provided time‐course changes and revealed several causes of knee OA onset and progression [ 4 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation